Quality-assessment expectations and quality-assessment reality in educational interpreting: An exploratory case study - Foster, Lenelle (Stellenbosch Papers in Linguistics Plus, 2014)
This article focuses on data obtained from three separate studies conducted during a four-year period at Stellenbosch University, a higher education institution in South Africa. All three studies centred on the simultaneous interpretation of undergraduate lectures. Various data sets were used to examine whether there would be a discrepancy between what lecturers in a particular academic department emphasised when they first considered the feasibility of this type of educational interpreting, and what they actually focused on when assessing the interpreters’ performance. Discrepancies and correlations in the quality criteria identified by lecturers were examined against a rubric taken from existing literature on interpreter assessment (notably that of Kurz (2002)). Using this information and augmenting it with comments from a similar assessment of the same material undertaken by experienced interpreters, these discrepancies and correlations are briefly discussed. Given the exploratory nature of this case study, few recommendations are made. However, the fact that the data from this study seem – in broad terms – to agree with studies conducted in the field of conference interpreting would seem to indicate that the discrepancy between stated and actual quality assessment criteria is real, and will require much more detailed study in an educational interpreting setting.